Deviance and Control in Communities with Perfect Surveillance - The Case of Second Life - John Tucker (Surveillance and Society, 2011)
V Wang, K Haines and J V Tucker, Deviance and Control in Communities with Perfect Surveillance - The Case of Second Life, Surveillance and Society, 9 (2011) (1/2) 31-46.